Pengembangan Augmented Reality 3D Berbasis Etnomatematika Gamelan Jawa Timur untuk Mengembangkan Kemampuan Visual-Spasial Siswa - Annizar, Anas Ma’ruf; Mukhlis, Mohammad; Hanum, Malika (Media Pendidikan Matematika, 2026)
Students’ understanding of geometric concepts at the junior secondary level (SMP/MTs) continues to face substantial challenges, particularly in visualization and spatial orientation. This study developed a 3D Augmented Reality (AR3D) learning medium integrated with the ethnomathematics of East Javanese gamelan to facilitate students’ exploration of three-dimensional geometric concepts through interactive and contextualized representations. The development followed the ADDIE model, comprising needs analysis, design, development, implementation, and evaluation stages. The AR3D medium enables object manipulation, observation from multiple perspectives, and the integration of mathematical patterns such as symmetry, transformations, and spatial relationships with the rhythmic and visual structures of gamelan instruments. The trial was conducted in two junior secondary schools in East Java, Indonesia, using a pretest–posttest design and involving expert validation and user responses to evaluate validity, practicality, and learning effectiveness. The results demonstrate that the developed medium meets the criteria of validity and practicality and is effective in enhancing students’ mathematical visual–spatial abilities. Through an immersive learning experience grounded in local cultural contexts, students were able to develop spatial understanding more accurately and flexibly. Overall, the findings confirm that AR3D learning media based on the ethnomathematics of East Javanese gamelan effectively promote students’ mathematical visual–spatial abilities while contributing to more meaningful and contextualized mathematics learning.